2021
DOI: 10.3389/fphys.2021.733928
|View full text |Cite
|
Sign up to set email alerts
|

Stroke-Related Mortality at Different Altitudes: A 17-Year Nationwide Population-Based Analysis From Ecuador

Abstract: Introduction: Worldwide, more than 5.7% of the population reside above 1,500 m of elevation. It has been hypothesized that acute short-term hypoxia exposure could increase the risk of developing a stroke. Studies assessing the effect of altitude on stroke have provided conflicting results, some analyses suggest that long-term chronic exposure could be associated with reduced mortality and lower stroke incidence rates.Methods: An ecological analysis of all stroke hospital admissions, mortality rates, and disabi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 76 publications
(94 reference statements)
1
22
1
Order By: Relevance
“…An altitude of residence ≥ 2500 masl was negatively and significantly associated with decreased Framingham 10-year risk scores. This finding is in agreement with that reported in studies conducted in high-altitude regions of Switzerland [ 30 ], Austria [ 31 ], Greece [ 32 ], the United States [ 33 ], and Ecuador [ 34 ], in which it was found that living in a high-altitude region has a protective effect on cardiovascular mortality and the incidence of cardiovascular events, especially coronary heart disease and stroke. From animal models, it is postulated that altitude has a cardioprotective effect due to biological mechanisms associated with hypobaric hypoxia.…”
Section: Discussionsupporting
confidence: 92%
“…An altitude of residence ≥ 2500 masl was negatively and significantly associated with decreased Framingham 10-year risk scores. This finding is in agreement with that reported in studies conducted in high-altitude regions of Switzerland [ 30 ], Austria [ 31 ], Greece [ 32 ], the United States [ 33 ], and Ecuador [ 34 ], in which it was found that living in a high-altitude region has a protective effect on cardiovascular mortality and the incidence of cardiovascular events, especially coronary heart disease and stroke. From animal models, it is postulated that altitude has a cardioprotective effect due to biological mechanisms associated with hypobaric hypoxia.…”
Section: Discussionsupporting
confidence: 92%
“…Study 14: An ecological analysis of all stroke hospital admissions, mortality rates and disability-adjusted life-years in Ecuador published by Ortiz-Prado et al in 2021 demonstrated that high-altitude populations had lower stroke mortality in men (OR 0.91, 95% CI 0.88 to 0.95) and women (OR 0.83, 95% CI 0.79 to 0.86) and had a significant lower risk of getting admitted to the hospital when compared with the low-altitude group in men (OR 0.55, 95% CI 0.54 to 0.56) and women (OR 0.65, 95% CI 0.64 to 0.66). 35 …”
Section: Resultsmentioning
confidence: 99%
“…Several anecdotal case reports and case series of people suffering from stroke-related disorders at high altitude have been published since the late 1800s 25. Despite this apparent relationship, very few well-conducted epidemiological studies have been conducted worldwide, and we have only included those studies that fulfilled our inclusion and exclusion criteria 14 15 20 21 26–36…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that at high-altitudes there is a lower expression of ACE-2 receptors, which are precisely the gateway to our cells for the SARS-CoV-2 virus [ 8 ]. A more plausible explanation goes along with the fact that high-altitude inhabitants express genes responsible for producing more erythrocytes (increasing oxygen transport) and creating new blood vessels (greater oxygen supply) [ 10 , 46 , 47 ]. On top of this, we must add certain anatomical and morphological characteristics among high-altitude dwellers, such as larger and bigger thoraxes as well as greater ventilatory capacities, that might play a role in reducing hypoxia found during severe ARDS due to COVID-19 [ 23 , 48 – 50 ].…”
Section: Discussionmentioning
confidence: 99%